2007
DOI: 10.1002/jms.1165
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐laser desorption/ionization on gold nanostructures

Abstract: In this report, we describe the visible-laser desorption/ionization of biomolecules deposited on gold-coated porous silicon and gold nanorod arrays. The porous silicon made by electrochemical etching was coated with gold using argon ion sputtering. The gold nanorod arrays were fabricated by electrodepositing gold onto a porous alumina template, and the subsequent partial removal of the alumina template. A frequency-doubled/tripled Nd : YAG laser was used to irradiate the gold nanostructured substrate, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Nakamura et al [28] reported similar results for the determination of asialo GM1 while 2,5-DHB was dissolved in acetonitrile/water (1:1, vol/vol). Because AuNPs have a small heating capacity, the heat diffusion from AuNPs to analyte is fast during the laser pulse [14]. Thus, the metastable heating of GM1 results in fragmentation (GM1 Ϫ Neu5Ac).…”
Section: Carbohydrates Gm1 Indolamines and Angiotensin Imentioning
confidence: 99%
See 1 more Smart Citation
“…Nakamura et al [28] reported similar results for the determination of asialo GM1 while 2,5-DHB was dissolved in acetonitrile/water (1:1, vol/vol). Because AuNPs have a small heating capacity, the heat diffusion from AuNPs to analyte is fast during the laser pulse [14]. Thus, the metastable heating of GM1 results in fragmentation (GM1 Ϫ Neu5Ac).…”
Section: Carbohydrates Gm1 Indolamines and Angiotensin Imentioning
confidence: 99%
“…It is suggested that cobalt NPs take the advantages of a large surface area, high photoabsorption, and low heat capacity compared with those of microparticles. Inspired by Tanaka's results, a series of inorganic micro-and nanomaterials-such as graphite particles [9], gold NPs (AuNPs) [10], silver NPs [11], titanium dioxide NPs [12], silicon NPs [13], Au nanorods [14], and carbon nanotubes [15]-have been studied as potential inorganic matrices. Moreover, matrix-free LDI-MS has been proposed using porous silicon as a sample target for the analysis of small molecules such as peptides, drugs, surfactants, and carbohydrates [16].…”
mentioning
confidence: 99%
“…17) Metal-oxide-based semiconductors with good UV absorbance are also promising candidates for matrix-free LDI-MS applications, such as titania sol-gel films, 18) titania nanotube arrays, 19) zinc oxide nanowires, 20) mesoporous tungsten titanium oxides, 21) and germanium nanodots. 22) In addition, double-or multilayer-coated hybrid substrates such as metal-coated porous alumina (platinum/alumina), 23), 24) two-layered amorphous silicon, 25) titaniaprinted aluminum foils (titania/aluminum), 26) silverparticle-deposited porous silicon (silver/silicon), 27) gold nanorods on porous alumina (gold/alumina), 28) layerby-layer (LBL) self-assembled films (polymer/gold), 29) Pt nanoflowers on a scratched silicon, 30) DVDs coated with diamond-like carbon, 31) and cationic-polymercoated graphite sheets (polymer/graphite) 32) are considered to be promising materials for matrix-free LDI-MS because the layer properties of these substances can be varied independently. Further, these hybridization e#ects can improve the e$ciency of matrix-free LDI-MS.…”
Section: )῍9)mentioning
confidence: 99%
“…In addition, the a-cyano-4-hydroxycinnanic acid coating on AuN�s effectively suppressed formation of Au cluster ions and analyte fragment ions, leading to a cleaner mass spectra. Another special property of AuN�s is their ability to absorb visible light owing to localized surface plasmon resonance (S�R) and visible-LDI with the assistance of AuN�s was developed [22][23][24]. Normally, a 532-nm visible laser, corresponding to the S�R of approximately 15 nm diameter gold nanospheres, is used instead of the typical UV laser of 337 and 355 nm.…”
Section: Nanomaterial-assisted Laser Desorption Ionizationmentioning
confidence: 99%